The impact of perceived brand integrity in increasing brand legitimacy in halal cosmetics among Muslim customers in Jakarta, Indonesia - Kartasasmita, Intan Kemala Hidayat; Kurniawati, Kurniawati (Universitas Islam Indonesia, 2024)
Introduction The rapid growth of halal cosmetic consumption has forced companies to compete in the Indonesian market. Many halal cosmetic companies use modern strategies that involve environmental concerns. Objectives This study aims to analyze the role of perceived brand ethics and environmentally friendly packaging in influencing brand legitimacy through perceptions of brand integrity in halal cosmetics. Method This research used quantitative methods. The research population was users of halal cosmetics, so a sample of 200 respondents was obtained using nonprobability sampling techniques. The questionnaires were distributed with five-point Likert-scale measurements. The analysis technique used in this study was structural equation modeling using IBM SPSS AMOS. Results The results prove that perceived brand ethics and environmentally friendly packaging have a positive effect on perceived brand integrity. Perceived brand integrity has a positive effect on brand legitimacy and can mediate the influence of perceived brand ethics on brand legitimacy. Implications The implication of this research is that it is hoped that companies will continue to improve their brand ethics by continuing to comply with brand ethics laws. Furthermore, it can provide education to consumers regarding environmentally friendly cosmetics and increase brand integrity through communities such as halal cosmetic brands. Originality/Novelty This study contributes to the literature on halal cosmetics in Indonesia, one of the largest Muslim markets.